If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 28 = 3x + 133 Reorder the terms: 28 + 10x = 3x + 133 Reorder the terms: 28 + 10x = 133 + 3x Solving 28 + 10x = 133 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 28 + 10x + -3x = 133 + 3x + -3x Combine like terms: 10x + -3x = 7x 28 + 7x = 133 + 3x + -3x Combine like terms: 3x + -3x = 0 28 + 7x = 133 + 0 28 + 7x = 133 Add '-28' to each side of the equation. 28 + -28 + 7x = 133 + -28 Combine like terms: 28 + -28 = 0 0 + 7x = 133 + -28 7x = 133 + -28 Combine like terms: 133 + -28 = 105 7x = 105 Divide each side by '7'. x = 15 Simplifying x = 15
| 6=m*3-9 | | 4xy+7y=4xy | | H*4+1=9 | | 12-6x=3/2 | | 3w+9x-12y+4w+3x+6y= | | N*10-20=0 | | 3x^2-48x+140=0 | | 30-x=3x+26 | | J*3+5=9 | | y=1/3x-1/5 | | 15-2x=4x-3 | | K*2+4=6 | | 8x-14=9x+6 | | 29.50=1.50x+7 | | 2*(x+1)=6 | | x^2(x^2-7x-18)=0 | | 20(X+8)=40X | | 2(X+8)=40X | | 6(-2-3)=6 | | X^2-4x-1152=0 | | 2(750-x)+3x=1750 | | (3x+11)-2x=19 | | 7(5-x)-3(-4-6x)=-8 | | w^2+0.11w=0.057 | | 3=-3x+29 | | 0.5x/x | | -4(5x-2)=4(2x-3) | | x=9x+40 | | -6d-3d+3=-12 | | 20x^3-40x=0 | | 7x-21y=-14 | | 6l+4m-5l-4m-l+m= |